Niger : 2019 Article IV Consultation, Fourth Review Under the Extended Credit Facility, and Requests for Waiver of Nonobservance of a Performance Criterion, Modification of Performance Criteria, and Extension and Rephasing of the Extended Credit Facility Arrangement-Press Release; Staff Report and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report ;, 2019)
This paper discusses Niger's 2019 Article IV Consultation, Fourth Review Under the Extended Credit Facility (ECF), and Requests for Waiver of Nonobservance of a Performance Criterion, Modification of Performance Criteria, and Extension and Rephasing of the ECF Arrangement. Program implementation has been broadly satisfactory with public finances strengthening as planned, progress with the implementation of the structural reform agenda, and some slippages in the clearance in domestic payment arrears. Improving public finances, mobilizing revenues, and improving spending quality remain high on the agenda. The Article IV consultation focused on ways to jump-start Niger's still embryonic local formal private sector and how to best foster good governance. Economic growth strengthened in 2018 and the outlook is promising thanks to the start of several large-scale projects by private investors and development partners. The review highlights that the formal local private sector needs strengthening to ensure sustainably higher living standards and provide jobs for Niger's rapidly growing labor force.